158k views
2 votes
Rewrite the expression in a simpler form. Be sure to show the steps in your work. (3a^5)(14a^8)

User MicroSumol
by
4.8k points

1 Answer

5 votes

Answer:


14a^(13)

Explanation:

Step 1 - Remove the parenthesis:


3a^5 * 14a^8

Step 2 - Multiply the whole numbers


3 * 14 = 42


42a^5a^8

Step 3 - Add the exponents together:


x^a * x^b = x^(a + b)


a^5 * a^8 = a^(5 + 8)

=
a^(13)

Step 4 - Put the two components back together:


14 + a^(13) = 14a^(13)

Hope this helps!

User Anish Karunakaran
by
5.3k points